Electrodeposition Combination with Hydrothermal Preparation of ZnO Films and Their Application in Dye-Sensitized Solar Cell - Xiaoping Zou; Yan Liu; Cuiliu Wei; Zongbo Huang; Xiangmin Meng (Journal of Chemistry)
A suitable method is necessary for the high performance of dyes-sensitized solar cells (DSSCs). In this paper, photoanodes of DSSCs have been fabricated through electrodeposition and combination with hydrothermal method. The results of mix method showed better performance than the single one. After the second step electrodeposition, the ZnO films formed flack finally. With the increase of hydrothermal time, ZnO films become thicker and bigger, which can offer large surface area to absorb much more dyes. The short-circuit current (2.4 mA/cm2) and open-circuit voltage (0.67 V) were greater than the single one, alternating current impedance indicating that electrodeposition and hydrothermal mix are a more suitable method for high performance DSSCs. We expected to obtain higher conversion efficiency of DSSCs by this method.